Representation and legitimation in streaming television's teenage girl traumedies - Barnes-Nelson, Madison, author; Marx, Nick, advisor; Elkins, Evan, committee member; Wolfgang, David, committee member (Colorado State University. Libraries, 2023)
My objects of study for this project are three streaming television series: Hulu's Pen15 (2019-2021), HBO Max's The Sex Lives of College Girls (2021-), and Channel 4/Netflix's Derry Girls (2018-2022). These series comprise a hybrid television genre I term "teenage girl traumedy." I argue that teenage girl traumedies lend teenage girl characters empathy and emotional complexity not historically afforded to them on television. Using these three series as case studies, I argue that the genre is legitimized culturally and industrially in two ways: 1) through textual appeals in narrative and visual form to feminist discourse and 2) paratextual branding in trade press and interviews with creators that centralize these series' feminist messages of teenage girls' trauma as a distinctive, competitive quality in streaming television. My three case studies depict emotional and bodily traumas on different levels, from the intimate and individualized, interpersonal and institutional, to the national. I show trauma growing and spreading as my thesis develops, as a way to show how teenage girl trauma manifests as personal shame and how the coping process for teenage girls bumps up against interpersonal, institutional, and national spheres. Industrially, my thesis explores the tension between creators who produce subversive, feminist art and the commercially driven streaming services that employ them. I am interested in understanding how these creators write television that delves into themes of young women's sexual and psychological trauma, developing out of previous decades of television that portrayed teenage girls as one-dimensional.